Conditioning Sexuality in A Young Adult Dystopian Fiction Lauren Oliver's Delirium - Surastini Surastini (Passage, 2016)
Sexuality has been regarded as one of the most prevalent issues in young adult literature. Its  relationship with physical and psychological development of adolescent is what makes the study  significant to be conducted. The present paper focuses on how sexuality is presented in a young  adult dystopian fiction, specifically by investigating how obliteration of sexual intimacy in  human relationship is conducted to create obedient society in Lauren Oliver‟s Delirium. In Delirium universe, the conduct of sexuality is considered as a threat since it stimulates bonding, attachment and love, which have the potential to inverse one‟s loyalty to the state. The analysis  of the qualitative descriptive study is framed by Tuzzeo (2008) study on psychological  conditioning which corresponds to Skinner (1971) study on human behavior. The analysis shows that there are three main strategies implemented by the government. They are creating new social order, obliterating bonding and sexual intimacy and implementing disciplinary system. Lastly, the study suggests the future research conductinganalysis of family representation in dystopian fiction. Keywords: sexuality, conditioning, young adult dystopian, Delirium